EVALUASI PROGRAM STUDI KEPERAWATAN PROGRAM PENDIDIKAN PROFESI NERS DI INSTITUSI X - Jesy Milanti (2021)
One of the institutions that has a professional nurse education program and almost 100% of graduates is the Pembangunan Nasional Veteran University, Jakarta. This study aims to see how effective the implementation of the Nursing Study Program is in the Nursing Professional Education Program organized by the Pembangunan Nasional Veteran, Jakarta. This research method uses a qualitative approach to the research design of the CIPPO Model Evaluation (Context, Input, Process, Product, and Outcome). Informants in this study were selected purposively with inclusion criteria and exclusion criteria. The number of participants in this study was six people consisting of the head of the nursing profession study program, academic precept, clinical precept (head of the room), and three students graduating in 2020. Data collection was carried out by in-depth interviews, observation, and document review. Data analysis was carried out by comparing data using evaluation criteria. The results of the evaluation of the Nursing Study Program for the Nursing Professional Education Program at the Pembangunan Nasional Veteran University, Jakarta, show that the implementation of the nursing professional education program has been effective. Researchers expect the nursing profession study program to conduct a tracer study of 100% of graduates by using an information system so that information is more easily accessed by every alumnus.